Você está na página 1de 9

Partial Dierential Equations I Tim Meagher 11/4/2010 Section 3.

2 Problem 1: For the following functions, sketch the Fourier series f(x) ( on the interval L x L). Compare f(x) to its Fourier series. b) f (x) = x2 The dotted line is f(x) and solid line is Fourier Series, and L=1

Problem 2: For the following functions, sketch the Fourier series f(x) ( on the interval L x L) and determine the Fourier coecients. c)f (x) = sin x L

a0 = an = bn =

L 1 x 2L L sin L dx = 0 L 1 xn x 1L L sin L cos L dx = 0 L xn 1 x 1L L sin L sin L dx = 1

if n=1 and 0 is n = 1

f) f (x) = {0 : x < 0; 1 : x > 0}

1 a0 = 2L 1 an = L 1 bn = L

L 1dx = 1 2 0 L L cos xn dx = Ln sin xn |L L L 0 0 L xn L sin L dx = Ln cos xn |L L 0 0

=0 2 = n if n is odd and 0 if n is even

Problem 4: Suppose that f(x) is piecewise smooth. What value of does the Fourier Series of f(x) converge to at the endpoint x=-L? and at x=L? The Fourier Series converges at the endpoints if f(-L)=f(L).

Section 3.3 Problem 1: For the following functions, sketch f(x), the Fourier series of f(x), the Fourier sine series of f(x), and the Fourier cosine series of f(x). d) f (x) = ex f(x):

Fourier Series:

Cosine Series:

Sine Series:

Problem 2: For the following functions, sketch the Fourier sine series of f(x) and determine tis Fourier coecients. d) f (x) = {1 : x < L/2; 0 : x > L/2} Sine Series:

bn =

2 L

L/2 0

sin xn dx = L

2L xn L/2 Ln cos L |0

2 n (1

cos n ) 2

Section 4.2 Problem 1: a) Using Equation (4.2.7), compute the sagged equilibrium position uE (x) if Q(x,t)=-g. The boundary conditions are u(O)=0 and u(L)=0
2 uE (x) = T0 uE2(x) g0 (x) t2 x 2 0 = T0 uE2(x) g0 (x) x 2 g0 (x) = uE2(x) T0 x Therefore, uE (x) = g0 (x) x2 + x + 2T0

0 (x)

Applying the boundary conditions: u(O)=0 g0 (x) (0)2 + (0) + = 0 = 0 2T0 u(L)=0 Therefore,
g0 (x) 2 2T0 (L) + L = 0 uE (x) = g0 (x) (x2 2T0

= g0 (x) (L) 2T0 xL)

b) Show that v(x, t) = u(x, t) uE (x) satises (4.2.9).


2 v 2 2 v t2 = c x2 2 2 (uuE ) = c2 (uuE ) t2 x2 2 2 2 (u) 2 (u) 2 (uE ) t2 = c x2 c x2 2 2 (u) (u) = c2 x2 g t2

Since for small g which is often the case it can be neglected. 2 2 (u) 2 (u) t2 = c x2 Problem 2: Show that c2 has dimensions of velocity squared. 5

c2 =

T0 0

Where T0 is a force and units


kg m s2 kg m

kg m s2

and 0 is a force and units

kg m

therefore c2 =

= ( m )2 . This is velocity squared. s

Sections 4.4 Problem 2: In section 4.2 it was shown that the displacement u of a nonuniform string satises 2 2 u 0 2 = T0 u + Q, t x2 Where Q represents the vertical component of the body force per unit length. If Q=0, the partial dierential equation is homogeneous. A slightly dierent homogeneous equation occurs if Q = u a)Show that if < 0, the body force is restoring (towards u=0). Show that if > 0, the body force tends to push the string further away from its unperturbed position u=0 If < 0 then for positive u, Q will be negative and when u is negative, Q will be positive, therefore u will tend towards 0. If > 0 then for positive u, Q will be positive and when u is negative, Q will be negative, therefore u will tend away 0.

b) Separate variables if 0 (x) and (x) but T0 is constant for physical reasons. Analyze the time-dependent ordinary dierential equation. 0 (x)
2 2

h(t)(x) t2

= T0

h(t)(x)

Therefore h(t) = c1 cos( t) + c2 sin( t) c) Specialize part (b) to the constant coecient case. Solve the initial value problem if < 0: u(0,t)=0 u(L,t)=0 u(x,0)=0 What are the frequencies of vibration?
u t (x, 0) 2 (h(t)) t2 2 ((x)) x2

h(t)(x) 1 t2 h(t) = 2 (h(t)) = h(t) t2

T0 x2 (x)(x)

x2 2 h(t)(x)

+ (x)h(t)(x)
(x)

= f (x).

= h(t) =
(x)(+ (x) )(x) T0

But this is the constant coecient case so 2 (h(t)) = h(t) t2


2 ((x)) x2

(x)(+ ) T0

Therefore (x) = c3 cos( x) + c4 sin( T0 Apply the boundary conditions we get

(+ )

(+ ) x) T0

(0) = 0 c3 cos( (L) = 0 c4 sin(

(+ ) 0) + c4 sin( (+) 0) = 0 T0 T0 (+ ) T0 n2 2 L2 L) = 0 = T0

C3 = 0

Meaning the Frequency is the square root of therefore T0 n L (Sorry for the (x) I oringinally solve with Q = up(x) looking at a dierent formula in the book, it was easier to write up replace the with (x) when doing a once over on the answers.)

Problem 3: Consider a slightly damped vibrating string that satises 2 2 u 0 2 = T0 u u , t x2 t a) Briey explain why > 0 Because if = 0 we have the homogenous case, which is ne, but not the point of the problem and if < 0 the string amplitudes would increase exponentially, giving a innite solutions as t went to innity, this can be seen by looking at the solution below.

b) Determine the solution (by separation of variables) that satises the boundary conditions u(0,t)=0 and u(L,t)=0 and the initial conditions u(x,0)=f(x) and u (x, 0) = g(x). t 0
2 h(t)(x) = T0 h(t)(x) h(t)(x) t2 x2 t 2 2 h(t)) (x) 1 1 + T0 h(t) h(t) = (x) x2 2 h(t) 2 c t t 2 (x) x2 = (x) 2

given these initial conditions we have solve before (even in this homework) n = sin( nx ) and n = ( n )2 L L Therefore we have
h(t)(x) t2
2

+ A miracle occurs (after a lot of work and getting lost, I look up the answer)
hn (t) = e 2 (cos( T0 ( n )2 ( 2 )2 ) + sin( L Putting the two together we get
2 t

2 h(t)(x) 1 T0 h(t) h(t) c2 h(t) t2 t h(t) + c2 ( n )2 h(t) = 0 t L

= ( n )2 L

T0 n 2 2 ( L )

( 2 )2 )

u(x, t) =

(e 2 (cos(
n=1

T0 n 2 2 ( ) ( )2 )+sin( L 2

T0 n 2 2 nx ( ) ( )2 ))sin( ) L 2 L

Problem 7: If a vibrating string satisfying (4.4.1)-(4.4.3) is initially at rest, g(x)=0 show that u(x, t) = 1 [F (x ct) + F (x + ct)], 2 Where F(x) the is the odd periodic extension of f(x). The general solution for this is as follows: nct nx nct nx )cos( ) + Bn sin( )sin( ) u(x, t) = An sin( L L L L n=1
2 Where An = L 2 nc and Bn L = L

however g(x)=0 all Bn = 0 nx nct Therefore u(x, t) = An sin( )cos( ) L L n=1


1 Note: sin(a)cos(b) = 2 [sin(a + b) + sin(a b) 1 nx + ct 1 nx ct Therefore u(x, t) = An sin( ) An sin( ) 2 L 2 L n=1

L f (x)sin( nx )dx L 0 L g(x)sin( nx )dx, L 0

Let F (x) =
n=1

An sin(

nx ) L

Thenu(x, t) = 1 [F (x ct) + F (x + ct)] 2 Problem 9: From(4.4.1), derive conservation of energy for a vibrating string. dE 2 u u L dt = c x t |0 , L where the total energy E is the sum of the kinetic energy, dened by 0 1 ( u )2 dx, 2 t L c2 u 2 and the potential energy, dened by 0 2 ( x ) dx.
1 E = 0 2 ( u )2 dx + 0 c2 ( u )2 dx. t x 2 L 1 u 2 E = 0 2 ( t ) + c2 ( u )2 dx x L 1 u 2 dE c2 u 2 dt = 0 2 t ( t ) + 2 t ( x ) dx After this I lost on the step from here to next step dE 2 u u L dt = c x t |0 , L L
2

Problem 10: What happens to the total energy E of a vibrating string a) If u(0,T)=0 and u(L,t)=0 The Total energy will remain constant as long Q(x,t) equals 0, and will os-

cillate between potential and kinetic energy. b)If


u x (0, t)

= 0 and u(L, t) = 0

The Total energy will oscillate but will be stable for there will be energy will stored and released in the spring at x=0